Harvest period and baking industry residue inclusion on production efficiency and chemical composition of tropical grass silage - Araújo, J. A.S.; Almeida, J. C.C.; Reis, R. A. [UNESP]; Carvalho, C. A.B.; Barbero, R. P. (Elsevier, 2020)
The seasonality of forage production is a challenge for livestock production in Brazil. Elephant grass (Pennisetum purpureum Schum.) silage is a widely cultivated forage however, this plant may represent high moisture levels and other unfavorable traits for ensiling and conservation during the ideal harvest period. The purpose of this experiment was to evaluate the effect of harvest period and the inclusion of bakery residue on silage traits and chemical composition. Elephant grass was harvested and ensiled into mini-silos 70, 84, and 98 days after regrowth, with the addition of 0, 5, 10, or 15% of bakery residue. After 45 days, the mini-silos were opened to evaluate the chemical composition and traits of the silage. The design was completely randomized in a full factorial arrangement with three harvest periods and four doses of bakery residue (3 × 4), with four replicates (mini-silos) per treatment (n = 48). The tests for all the assumptions of variance analyses were conducted. The effects of harvest period (days) and concentration of residue (%) were evaluated using orthogonal polynomial contrasts, adopting the polynomial with a greater degree of significance (p < 0.05). Harvest period did not influence the dry matter content of elephant grass silage (p = 0.2126). Similarly, the inclusion of bakery residue in elephant grass silages did not affect the pH (p = 0.1466); however, it linearly increased the temperature (p < 0.0001), NH3/N total (p < 0.0001), non-fibrous carbohydrates (p = 0.0024), and dry matter recovery (p < 0.0001). The increases in bakery residue linearly reduced (p = 0.0497) effluent production of elephant grass harvested at 70 days. The inclusion of bakery residue in elephant grass silages decreased the neutral (p < 0.0001) and acid detergent fiber (p < 0.0001) levels. The inclusion of bakery residue decreases effluent production, increases dry matter recovery, and improves the chemical composition of elephant grass silage.
Keywords: Animal nutrition; Bakery residue; Elephant grass; Pennisetum purpureum Schum